1992
DOI: 10.1029/92gl01276
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of observed diurnal and semidiurnal tropospheric winds at Christmas Island with tidal theory

Abstract: Four years of hourly averaged atmospheric wind measurements from the Christmas Island VHF wind profiler were processed into typical days to show the vertical phase structure of the diurnal and semidiurnal tropospheric zonal winds. The winds from the lowest resolvable height were compared with both the surface winds calculated from a three year record of surface pressure using the equations of motion on a rotating, frictionless sphere, and the winds from a tidal model. It is concluded that at the lowest height,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…Similar horizontal wind amplitudes of the diurnal tide have been observed with radiosonde from western Pacific sites [ Tsuda et al , 1995, 1997] and with tropical Pacific wind profilers [ Williams and Avery , 1996]. On the basis of a 4 year composite of tidal winds from a wind profiler in the equatorial Pacific, Williams et al [1992] concluded that the diurnal and semidiurnal tides were predominantly migrating. The phases and amplitudes of the diurnal tides were reported to undergo relatively little seasonal variation in the troposphere [ Williams and Avery , 1996].…”
Section: Discussionsupporting
confidence: 71%
“…Similar horizontal wind amplitudes of the diurnal tide have been observed with radiosonde from western Pacific sites [ Tsuda et al , 1995, 1997] and with tropical Pacific wind profilers [ Williams and Avery , 1996]. On the basis of a 4 year composite of tidal winds from a wind profiler in the equatorial Pacific, Williams et al [1992] concluded that the diurnal and semidiurnal tides were predominantly migrating. The phases and amplitudes of the diurnal tides were reported to undergo relatively little seasonal variation in the troposphere [ Williams and Avery , 1996].…”
Section: Discussionsupporting
confidence: 71%
“…The semidiurnal amplitudes reported in this study (0.2-0.5 m s À1 ) are consistent with those in the lower troposphere over the USA (0.2-0.5 m s À1 ) (Fig. 8 in Whiteman and Bian 1996), but larger than those in the tropics (@0.2 m s À1 ) (Williams et al 1992). The occurrence of larger amplitudes in midlatitude regions is consistent with the theoretical prediction Based on the above results, the seasonal variation in semidiurnal amplitudes shown in Fig.…”
Section: B Eastward-moving Phenomenasupporting
confidence: 76%
“…Few studies have provided a broader viewpoint of ''diurnal wind variations in the troposphere,'' including local wind systems. These few studies were based mainly on tropical observations, either intensive radiosonde campaigns (Tsuda et al 1994;Alexander and Tsuda 2008) or atmospheric radars (Williams et al 1992;Chen et al 1996;Williams and Avery 1996b;Sasi et al 1998Sasi et al , 2001Riggin et al 2002), and investigated the diurnal and semidiurnal wind components by focusing on atmospheric tides and local wind systems.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, wind profilers with RASS (Radio Acoustic Sounding System) were constructed on several islands, providing wind and temperature profiles with higher time and height resolutions and reliability than those previously obtained in this important region. Many of the profilers used in the TOGA COARE TOP were VHF band radars with a standard operational altitude range of 2-18 km (Balsley et al, 1987(Balsley et al, , 1991Gage et al, 1988Gage et al, , 1991aGage et al, , b, 1994Williams et al, 1992;Sukmadradjat et al, 1993). The other type of wind profilers were UHF band radars which were used for altitudes lower than 5 km (Ecklund et al, 1988(Ecklund et al, , 1990May and Wilczak, 1993).…”
Section: Introductionmentioning
confidence: 99%